Graphitization furnace and battery production equipment

By providing an wear-resistant conductive layer composed of a binder, conductive agent and wear-resistant filler on the first electrode of the graphitization furnace, the problem of short service life of the graphitization furnace is solved, and more efficient and stable battery production is achieved.

CN119554868AActive Publication Date: 2025-03-04NINGDE XICHENG TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510105398.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-03-04
Estimated Expiration
2045-01-23

AI Technical Summary

Technical Problem

The service life of existing graphitization furnaces is short, resulting in inefficient battery production and manufacturing.

Method used

A first wear-resistant conductive layer is provided on the first electrode of the graphitizing furnace, which consists of a first adhesive, a first conductive agent and a first wear-resistant filler to improve the wear resistance and conductivity of the electrode, and isolate the direct contact between oxygen and the electrode.

Benefits of technology

By improving the wear resistance and conductivity of the first electrode, the service life of the graphitization furnace is extended and the efficiency and stability of battery production are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119554868A_ABST
    Figure CN119554868A_ABST
Patent Text Reader

Abstract

The invention provides a graphitization furnace and battery production equipment, and the graphitization furnace comprises a furnace body which is internally provided with a material channel; the first electrode is arranged in the extending direction of the material channel and is partially located in the material channel; the first electrode comprises a base body and a first wear-resistant conductive layer arranged on the surface of the base body; the polarity of the second electrode is opposite to that of the first electrode; the second electrode extends into the material channel and is spaced from the first electrode. The graphitization furnace has a relatively long service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of battery production equipment, and in particular to a graphitization furnace and battery production equipment. Background Art

[0002] In recent years, as the application scope of battery technology has become wider and wider, batteries are widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as in many fields such as power tools, electric bicycles, electric motorcycles and electric vehicles.

[0003] At present, carbon materials are widely used in negative electrode materials of batteries. Among them, graphitized carbon materials (also referred to as graphite materials) have been widely used in commercial applications due to their long service life, stable structure, low cost and other advantages. Graphitization furnace is a kind of equipment that can generate graphite materials. Its service life is very important for the production and manufacturing of graphite and batteries.

[0004] In view of this, how to improve the service life of the graphitization furnace is a technical problem that needs to be solved urgently. Summary of the invention

[0005] The present application is made in view of the above-mentioned problems, and one of its purposes is to provide a graphitization furnace and a battery production device, wherein the graphitization furnace has a long service life.

[0006] In order to achieve the above object, the first aspect of the present application provides a graphitization furnace, comprising:

[0007] A furnace body, wherein a material channel is arranged in the furnace body;

[0008] A first electrode is arranged along the extension direction of the material channel and is partially located in the material channel; the first electrode comprises a substrate and a first wear-resistant conductive layer arranged on the surface of the substrate;

[0009] The second electrode has a polarity opposite to that of the first electrode; the second electrode extends into the material channel and is spaced apart from the first electrode.

[0010] By providing a first wear-resistant conductive layer on the surface of the substrate of the first electrode, the wear resistance of the first electrode can be effectively improved, and the wear on the first electrode caused by the material in the material channel flowing downward along the first electrode can be reduced; at the same time, good conductivity can be provided to effectively heat the material to graphitize it; and the first wear-resistant conductive layer can effectively isolate the direct contact between oxygen and the first electrode, and alleviate the oxidation of the part of the first electrode corresponding to the insertion port. By providing the above-mentioned first wear-resistant conductive layer, the service life of the first electrode can be effectively extended, thereby improving the service life of the graphitization furnace.

[0011] In any embodiment, the first wear-resistant conductive layer includes a first binder, a first conductive agent and a first wear-resistant filler. Thus, the first wear-resistant conductive layer contains the first conductive agent and the first wear-resistant filler, has good conductivity and can improve the wear resistance of the first electrode.

[0012] In any embodiment, the first binder includes one or more of phenolic resin, epoxy resin, bismaleimide resin, vinyl resin and cyanate ester resin.

[0013] In any embodiment, the first conductive agent includes one or more of a carbon material, a metal material, and a conductive polymer.

[0014] In any embodiment, the first wear-resistant filler includes one or more of poly-L-glutamate graphene composite, boron carbide, silicon carbide, metal powder and aluminum oxide powder.

[0015] In any embodiment, the carbon material includes one or more of graphene, graphene oxide, carbon fiber and carbon nanotube; the metal material includes one or more of silver powder, copper powder, silver fiber and copper fiber.

[0016] The first wear-resistant conductive layer is composed of the first adhesive, the first conductive agent and the first wear-resistant filler, which is conducive to making the first wear-resistant conductive layer have good wear resistance and conductivity.

[0017] In any embodiment, the mass ratio of the first binder, the first conductive agent and the first wear-resistant filler is 1-3:5-7:2-4. This is conducive to making the first wear-resistant conductive layer have good wear resistance and conductivity, and a lower friction coefficient, thereby helping to extend the service life of the first electrode and the graphitization furnace.

[0018] In any embodiment, the thickness of the first wear-resistant conductive layer is 30 μm to 200 μm. This is beneficial to improving the wear resistance of the first electrode, delaying oxidation and wear of the first electrode, and thus extending the service life of the first electrode.

[0019] In any embodiment, the thermal expansion coefficient of the first wear-resistant conductive layer is 10×10 -6 / ℃~100×10 -6 / °C. In this way, the first wear-resistant conductive layer has a smaller thermal expansion coefficient and is less likely to crack and fail.

[0020] In any embodiment, the first wear-resistant conductive layer is rotated 9000 to 11000 times at 23±2°C and 50±5% relative humidity. Thus, the first wear-resistant conductive layer has good wear resistance, can effectively improve the ability of the first electrode to resist material erosion, and improve the service life of the first electrode.

[0021] In any embodiment, the friction coefficient of the first wear-resistant conductive layer is 0.2-0.4. Thus, the first wear-resistant conductive layer has a smaller friction coefficient, which is beneficial to further reduce the wear of the first electrode during the material flow in the material channel, thereby facilitating the improvement of the service life of the first electrode.

[0022] In any embodiment, the conductivity of the first wear-resistant conductive layer is 50 μS / cm-1000 mS / cm. Thus, the first wear-resistant conductive layer has a suitable conductivity, which is conducive to introducing current into the material to heat the material.

[0023] In any embodiment, the first electrode further includes a second wear-resistant conductive layer, and the second wear-resistant conductive layer is disposed between the substrate and the first wear-resistant conductive layer. Thus, the second wear-resistant conductive layer is disposed between the first wear-resistant conductive layer and the substrate to form a double coating structure, which is beneficial to further improve the wear resistance and oxidation resistance of the first electrode and extend the service life of the first electrode and the graphitization furnace.

[0024] In any embodiment, the material of the second wear-resistant conductive layer includes a second binder, a second conductive agent and a second wear-resistant filler. Thus, by combining the second wear-resistant conductive layer with the first wear-resistant conductive layer, the service life of the first electrode can be effectively extended.

[0025] In any embodiment, the second binder includes one or more of phenolic resin, epoxy resin, bismaleimide resin, vinyl resin and cyanate ester resin.

[0026] In any embodiment, the second conductive agent includes one or more of a carbon material, a metal material, and a conductive polymer.

[0027] In any embodiment, the second wear-resistant filler includes one or more of poly-L-glutamate graphene composite, boron carbide powder, silicon carbide powder, metal powder and aluminum oxide powder.

[0028] In any embodiment, the carbon material includes one or more of graphene, graphene oxide, carbon fiber and carbon nanotube; the metal material includes one or more of silver powder, copper powder, silver fiber and copper fiber.

[0029] The second wear-resistant conductive layer is composed of the second adhesive, the second conductive agent and the second wear-resistant filler, which is conducive to making the second wear-resistant conductive layer have good wear resistance and conductivity.

[0030] In any embodiment, the mass ratio of the second binder, the second conductive agent and the second wear-resistant filler is 2-4:4-8:1-2. This is conducive to making the second wear-resistant conductive layer have better wear resistance and better conductivity.

[0031] In any embodiment, the thickness ratio of the second wear-resistant conductive layer to the first wear-resistant conductive layer is 1:1-8.7. In this way, the thickness of the first wear-resistant conductive layer is equal to or greater than the thickness of the second wear-resistant conductive layer, which is conducive to making the first wear-resistant conductive layer have better wear resistance and extending the service life of the first electrode.

[0032] In any embodiment, the thickness ratio of the second wear-resistant conductive layer to the first wear-resistant conductive layer is 1:1-4.3. Thus, making the thickness of the first wear-resistant conductive layer equal to or thicker than that of the second wear-resistant conductive layer is more conducive to extending the service life of the first electrode.

[0033] In any embodiment, the thickness of the second wear-resistant conductive layer is 20 μm to 40 μm, which, combined with the first wear-resistant conductive layer of a specific thickness, is conducive to extending the service life of the first electrode.

[0034] In any embodiment, the ratio of the thermal expansion coefficient of the second wear-resistant conductive layer to the first wear-resistant conductive layer is 1:1-1.5. This is more conducive to alleviating the cracking of the coating under the high temperature environment in the material channel, and can better take into account the expansion generated inside, which is conducive to the release of the internal expansion force and is more conducive to extending the service life of the first electrode.

[0035] In any embodiment, the ratio of the thermal expansion coefficients of the second wear-resistant conductive layer to the first wear-resistant conductive layer is 1:1-1.2. In this way, the second wear-resistant conductive layer and the first wear-resistant conductive layer can be better matched, and the internal expansion force can be released to alleviate the cracking of the coating.

[0036] In any embodiment, the thermal expansion coefficient of the second wear-resistant conductive layer is 5×10 -6 / ℃~30×10 -6 / °C. In this way, the second wear-resistant conductive layer has a suitable thermal expansion coefficient, and combined with the first wear-resistant conductive layer with a specific thermal expansion coefficient, the first electrode can have a longer service life.

[0037] In any embodiment, the second wear-resistant conductive layer rotates 6000 to 8000 times at 23±2°C and 50±5% relative humidity. In this way, the second wear-resistant conductive layer has good wear resistance, which is beneficial to resist the erosion of the first electrode by the material and improve the service life of the first electrode.

[0038] In any embodiment, the friction coefficient of the second wear-resistant conductive layer is 0.3-0.6.

[0039] In any embodiment, the conductivity of the second wear-resistant conductive layer is 10 μS / cm to 500 μS / cm. Thus, the second wear-resistant conductive layer has a relatively high conductivity, which is conducive to introducing current into the material to heat the material.

[0040] In any embodiment, the second electrode extends in a radial direction of the material channel.

[0041] In any embodiment, the number of the second electrodes is multiple, and the multiple second electrodes are arranged at intervals along the circumference of the material channel. This is conducive to making the electric field distribution in the cross section of the material channel more uniform, and is conducive to improving the uniformity of graphitization of the material.

[0042] In any embodiment, the first electrode is a positive electrode, and the second electrode is a negative electrode.

[0043] The second aspect of the present application provides a battery production device, comprising the graphitization furnace of the first aspect of the present application, wherein the graphitization furnace is used to produce negative electrode graphite material for the battery.

[0044] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] In order to better describe and illustrate the embodiments or examples provided by the present application, reference may be made to one or more drawings. The additional details or examples used to describe the drawings should not be considered as limiting the scope of the disclosed application, the embodiments or examples currently described, and any of the best modes of these applications currently understood. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:

[0046] FIG1 is a schematic structural diagram of a graphitization furnace according to an embodiment of the present application;

[0047] FIG2 is an enlarged structural diagram of a first electrode in a graphitization furnace according to an embodiment of the present application.

[0048] Description of reference numerals:

[0049] 100. Graphitization furnace; 110. Furnace body; 111. Material channel; 120. First electrode; 121. Matrix; 122. First wear-resistant conductive layer; 123. Second wear-resistant conductive layer; 130. Second electrode; 140. Power supply; 151. Material bin; 152. Material pipe; 153. Material shut-off valve; 160. Tail gas treatment unit; 170. Cooling and discharging unit. DETAILED DESCRIPTION

[0050] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0051] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0052] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0053] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0054] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0055] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).

[0056] In the description of the embodiments of the present application, the technical terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, which are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the embodiments of the present application.

[0057] In the description of the embodiments of the present application, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, and it can be the internal connection of two elements or the interaction relationship between two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.

[0058] The "range" disclosed in the present application can be limited in the form of a lower limit and an upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The range limited in this way can be including or excluding end values, and any end value can be included or not included independently, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a specific parameter, it is understood that the range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are also listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents the abbreviation of any real number combination between a and b, wherein a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to listing the parameter as, for example, integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc. For example, when a parameter is expressed as an integer selected from "2-10", it is equivalent to listing the integers 2, 3, 4, 5, 6, 7, 8, 9 and 10.

[0059] In the present application, in the open technical features or technical solutions described by the words "contain", "include", "comprise", etc., unless otherwise specified, additional members other than the listed members are not excluded, and it can be regarded as providing both closed features or solutions consisting of the listed members and open features or solutions including additional members in addition to the listed members. For example, A includes a1, a2 and a3. Unless otherwise specified, it may also include other members or may not include additional members. It can be regarded as providing both the feature or solution of "A consists of a1, a2 and a3" and the feature or solution of "A not only includes a1, a2 and a3, but also includes other members". In the present application, unless otherwise specified, A (such as B) means that B is a non-limiting example of A, and it can be understood that A is not limited to B.

[0060] In this application, "optionally", "optional", and "optional" mean optional, that is, any one of the two parallel schemes of "yes" or "no". If there are multiple "options" in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "option" is independent.

[0061] At present, carbon materials are widely used in negative electrode materials of batteries, among which graphitized carbon materials have been widely used in commercial applications due to their advantages such as long service life, stable structure and low cost. Graphitization furnace is a kind of equipment that can generate graphite materials, and its service life is very important for the production and manufacturing of graphite and batteries.

[0062] In the production process of the continuous graphitization furnace, the positive electrode is inserted from the material feed end along the extension direction of the material channel into the core temperature zone of the material channel of the furnace body, and the negative electrode is inserted into the material channel from the side of the furnace body. The positive electrode and the negative electrode are spaced apart. After power is turned on, an electric field is generated in the material channel. When the material in the material channel passes through the electric field, Joule heat will be generated due to its own resistance, thereby forming a high-temperature area. After passing through the high-temperature area, the material can be graphitized.

[0063] The upper end of the positive electrode of the graphitization furnace usually needs to extend out of the furnace body and be electrically connected to the power supply. During the operation of the continuous graphitization furnace, there is generally a slight negative pressure inside the furnace. A small amount of air will enter the material channel from the insertion port of the positive electrode, and the temperature in the material channel is relatively high, which makes the positive electrode (usually a graphite electrode) at the insertion port easily oxidized, causing the positive electrode portion corresponding to the insertion port to gradually oxidize and become smaller. When it reaches a certain level, the lower end of the positive electrode may fall into the furnace, affecting the service life of the graphitization furnace.

[0064] In addition, in the production process of the continuous graphitization furnace, the bottom of the positive electrode is close to the core temperature zone in the material channel, and the material in the material channel flows downward along the positive electrode. During the flow of the material, the positive electrode will be greatly worn, which will also reduce the service life of the positive electrode.

[0065] Based on this, please refer to FIG. 1 and FIG. 2 , an embodiment of the present application provides a graphitization furnace 100, which includes a furnace body 110, a first electrode 120, and a second electrode 130. Among them, a material channel 111 is arranged in the furnace body 110, and the material channel 111 extends from the upper part to the lower part of the furnace body 110; the first electrode 120 is arranged along the extension direction of the material channel 111 and is partially arranged in the material channel 111; the first electrode 120 includes a substrate 121 and a first wear-resistant conductive layer 122 arranged on the surface of the substrate 121; the second electrode 130 has an opposite polarity to the first electrode 120; the second electrode 130 extends into the material channel 111 and is arranged with a gap from the first electrode 120.

[0066] The graphitization furnace 100 of the present application can effectively improve the wear resistance of the first electrode 120 and reduce the wear of the material in the material channel 111 on the substrate 121 when the material flows downward along the first electrode 120 by providing the first wear-resistant conductive layer 122 on the surface of the substrate 121; at the same time, it can provide good conductivity to effectively heat the material to graphitize it; and the first wear-resistant conductive layer 122 can effectively isolate the direct contact between oxygen and the substrate 121, and alleviate the oxidation of the part of the substrate 121 corresponding to the insertion port. Through the above-mentioned first wear-resistant conductive layer 122, the service life of the first electrode 120 can be effectively extended, thereby improving the service life of the graphitization furnace 100.

[0067] It should be noted that the first electrode 120 is a positive electrode and the second electrode 130 is a negative electrode. Both the first electrode 120 and the second electrode 130 can be graphite electrodes. The graphitization furnace 100 also includes a power supply 140, and the first electrode 120 and the second electrode 130 are connected to the positive electrode and the negative electrode of the power supply 140, respectively. If the graphitization furnace 100 is arranged in a vertical manner, that is, the material channel 111 is arranged vertically, and the material flows downward along the material channel 111 under the action of gravity, which is consistent with the natural flow law of the object, then the first electrode 120 extends in the vertical direction. If the graphitization furnace 100 is arranged in a horizontal manner, that is, the material channel is arranged horizontally, and the material flows along the material channel 111 in the horizontal direction, then the first electrode 120 extends in the horizontal direction. FIG. 1 shows a vertical graphitization furnace 100, in which the extension direction of the material channel 111 in the graphitization furnace 100 is the vertical direction.

[0068] It can be understood that the first wear-resistant conductive layer 122 refers to a coating having good wear resistance and good conductivity.

[0069] In some embodiments, the first wear-resistant conductive layer 122 includes a first binder, a first conductive agent, and a first wear-resistant filler. The first binder includes one or more of phenolic resin, epoxy resin, bismaleimide resin, vinyl resin, and cyanate resin. The first conductive agent includes one or more of carbon materials, metal materials, and conductive polymers. The carbon material includes one or more of graphene, graphene oxide, carbon fiber, and carbon nanotubes; the metal material includes one or more of silver powder, copper powder, silver fiber, and copper fiber. The first wear-resistant filler includes one or more of poly-L-glutamic acid graphene composite, boron carbide powder, silicon carbide powder, metal powder, and aluminum oxide powder.

[0070] By using the first binder, the first conductive agent and the first wear-resistant filler to form the first wear-resistant conductive layer 122, the first wear-resistant conductive layer 122 can have good wear resistance and conductivity, a small friction coefficient and good surface sliding properties. By providing the first wear-resistant conductive layer 122 on the surface of the substrate 121, it is beneficial to make the first electrode 120 and the graphitization furnace 100 have a longer service life.

[0071] In some embodiments, the mass ratio of the first binder, the first conductive agent and the first wear-resistant filler in the first wear-resistant conductive layer 122 is 1-3: 5-7: 2-4. Controlling each component within the above range is conducive to making the first wear-resistant conductive layer 122 have better wear resistance and conductivity, lower friction coefficient and better surface sliding property; it is conducive to extending the service life of the first electrode 120 and the graphitization furnace 100.

[0072] In some embodiments, the thickness of the first wear-resistant conductive layer 122 is 30 μm to 200 μm. Controlling the thickness of the first wear-resistant conductive layer 122 within the above range is conducive to improving the wear resistance of the first electrode 120, delaying oxidation and wear of the first electrode 120, and thus extending the service life of the first electrode 120.

[0073] It can be understood that the thickness of the first wear-resistant conductive layer 122 can be 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 110μm, 120μm, 130μm, 140μm, 150μm, 160μm, 170μm, 180μm, 190μm, 200μm and any value within the range formed by any two of the above values.

[0074] In some embodiments, the thermal expansion coefficient of the first wear-resistant conductive layer 122 is 10×10 -6 / ℃~100×10 -6In this way, the first wear-resistant conductive layer 122 has a smaller thermal expansion coefficient, and when the temperature in the material channel 111 is high, the first wear-resistant conductive layer 122 is less likely to crack and fail.

[0075] It can be understood that the thermal expansion coefficient of the first wear-resistant conductive layer 122 can be 10×10 -6 / ℃、20×10 -6 / ℃、30×10 -6 / ℃、40×10 -6 / ℃、50×10 -6 / ℃、60×10 -6 / ℃、70×10 -6 / ℃、80×10 -6 / ℃、90×10 -6 / ℃、100×10 -6 / °C and any value within the range formed by any two of the above values.

[0076] In some embodiments, the first wear-resistant conductive layer 122 rotates 9000 to 11000 times at 23±2°C and 50±5% relative humidity. Thus, the first wear-resistant conductive layer 122 has good wear resistance, can effectively improve the ability of the first electrode 120 to resist material erosion, and improve the service life of the first electrode 120.

[0077] In some embodiments, the friction coefficient of the first wear-resistant conductive layer 122 is 0.2-0.4. Thus, the first wear-resistant conductive layer 122 has a smaller friction coefficient and its surface has better sliding properties, which is beneficial to further reduce the wear of the substrate 121 during the material flow in the material channel 111, thereby facilitating the improvement of the service life of the first electrode 120.

[0078] It can be understood that the friction coefficient of the first wear-resistant conductive layer 122 can be 0.2, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.3, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.4 and any value within the range formed by any two of the above values.

[0079] In some embodiments, the conductivity of the first wear-resistant conductive layer 122 is 50 μS / cm to 1000 mS / cm. Thus, the first wear-resistant conductive layer 122 has a suitable conductivity, which can effectively connect the contact part between the substrate 121 and the power source 140, and is conducive to introducing current into the material to heat the material.

[0080] It can be understood that the conductivity of the first wear-resistant conductive layer 122 can be 50μS / cm, 100μS / cm, 500μS / cm, 1mS / cm, 10mS / cm, 100mS / cm, 300mS / cm, 500mS / cm, 800mS / cm, 1000mS / cm and any value within the range formed by any two of the above values.

[0081] In some embodiments, the first electrode 120 further includes a second wear-resistant conductive layer 123, and the second wear-resistant conductive layer 123 is disposed between the substrate 121 and the first wear-resistant conductive layer 122. By disposing the second wear-resistant conductive layer 123 on the inner side of the first wear-resistant conductive layer 122, a double coating structure is formed, which is beneficial to further improve the wear resistance and oxidation resistance of the first electrode 120, and further extend the service life of the first electrode 120 and the service life of the graphitization furnace 100.

[0082] It can be understood that the second wear-resistant conductive layer 123 refers to a coating having good wear resistance and good conductivity.

[0083] In some embodiments, the material of the second wear-resistant conductive layer 123 includes a second binder, a second conductive agent, and a second wear-resistant filler. The second binder includes one or more of phenolic resin, epoxy resin, bismaleimide resin, vinyl resin, and cyanate resin; the second conductive agent includes one or more of carbon material, metal material, and conductive polymer; the carbon material includes one or more of graphene, graphene oxide, carbon fiber, and carbon nanotube; the metal material includes one or more of silver powder, copper powder, silver fiber, and copper fiber. The second wear-resistant filler includes one or more of poly-L-glutamic acid graphene composite, boron carbide powder, silicon carbide powder, metal powder, and aluminum oxide powder. In this way, by using the second wear-resistant conductive layer 123 composed of the above-mentioned second binder, second conductive agent, and second wear-resistant filler, combined with the first wear-resistant conductive layer 122, the service life of the first electrode 120 can be effectively extended.

[0084] In some embodiments, the mass ratio of the second binder, the second conductive agent and the second wear-resistant filler in the second wear-resistant conductive layer 123 is 2-4:4-8:1-2. This is conducive to making the second wear-resistant conductive layer 123 have better wear resistance and better conductivity.

[0085] In some embodiments, the thickness ratio of the second wear-resistant conductive layer 123 to the first wear-resistant conductive layer 122 is 1:1-8.7. In this way, the thickness of the first wear-resistant conductive layer 122 is equal to or greater than the thickness of the second wear-resistant conductive layer 123, which is conducive to making the first wear-resistant conductive layer 122 have better wear resistance, and is conducive to better maintaining the double-layer coating structure of the first electrode 120 during use, which is conducive to extending the service life of the first electrode 120.

[0086] It can be understood that the thickness ratio of the second wear-resistant conductive layer 123 to the first wear-resistant conductive layer 122 can be 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:8.7 and any ratio within the range formed by any two of the above ratios.

[0087] Optionally, a thickness ratio of the second wear-resistant conductive layer 123 to the first wear-resistant conductive layer 122 is 1:1-4.3.

[0088] In some embodiments, the thickness of the second wear-resistant conductive layer 123 is 20 μm to 40 μm. In this way, combined with the first wear-resistant conductive layer 122 having a thickness of 30 μm to 200 μm, it is beneficial to extend the service life of the first electrode 120. It is understandable that the thickness of the second wear-resistant conductive layer 123 can be 20 μm, 21 μm, 22 μm, 23 μm, 24 μm, 25 μm, 26 μm, 27 μm, 28 μm, 29 μm, 30 μm, 31 μm, 32 μm, 33 μm, 34 μm, 35 μm, 36 μm, 37 μm, 38 μm, 39 μm, 40 μm, and any value within the range formed by any two of the above values.

[0089] In some embodiments, the ratio of the thermal expansion coefficient of the second wear-resistant conductive layer 123 to that of the first wear-resistant conductive layer 122 is 1:1 to 1.5. In this way, the thermal expansion coefficients of the second wear-resistant conductive layer 123 and the first wear-resistant conductive layer 122 are close, so that the second wear-resistant conductive layer 123 and the first wear-resistant conductive layer 122 can be better matched, which is more conducive to alleviating the cracking of the coating under the high temperature environment in the material channel 111, and is conducive to extending the service life of the first electrode 120. Setting the thermal expansion coefficient of the first wear-resistant conductive layer 122 to be equal to that of the second wear-resistant conductive layer 123, or slightly larger than the thermal expansion coefficient of the second wear-resistant conductive layer 123, can better take into account the expansion generated inside, which is conducive to the release of the internal expansion force.

[0090] It can be understood that the thermal expansion coefficient ratio of the second wear-resistant conductive layer 123 to the first wear-resistant conductive layer 122 can be 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, and any ratio within the range formed by any two of the above ratios.

[0091] Optionally, the thermal expansion coefficient ratio of the second wear-resistant conductive layer 123 to the first wear-resistant conductive layer 122 is 1:1-1.2. In this way, the second wear-resistant conductive layer 123 and the first wear-resistant conductive layer 122 can be better matched, and the internal expansion force is released, which alleviates the cracking of the coating.

[0092] In some embodiments, the thermal expansion coefficient of the second wear-resistant conductive layer 123 is 5×10 -6 / ℃~30×10 -6 / ° C. In this way, the second wear-resistant conductive layer 123 has a suitable thermal expansion coefficient, and combined with the first wear-resistant conductive layer 122 with a specific thermal expansion coefficient, the first electrode 120 can have a longer service life.

[0093] It is understandable that the thermal expansion coefficient of the second wear-resistant conductive layer 123 may be 5×10 -6 / ℃、8×10 -6 / ℃、10×10 -6 / ℃、12×10 -6 / ℃、15×10 -6 / ℃、18×10 -6 / ℃、20×10 -6 / ℃、22×10 -6 / ℃、25×10 -6 / ℃、28×10 -6 / ℃、30×10 -6 / °C and any value within the range formed by any two of the above values.

[0094] In some embodiments, the second wear-resistant conductive layer 123 is rotated 6000 to 8000 times at 23±2°C and 50±5% relative humidity. Thus, the second wear-resistant conductive layer 123 has good wear resistance, which is beneficial to resist the erosion of the substrate 121 by the material, and is beneficial to prolonging the service life of the first electrode 120.

[0095] In some embodiments, the friction coefficient of the second wear-resistant conductive layer 123 is 0.3-0.6. In this way, the second wear-resistant conductive layer 123 has a smaller friction coefficient, and when the first wear-resistant conductive layer 122 is worn, the second wear-resistant conductive layer 123 can still keep the surface of the first electrode 120 with good sliding properties, which is beneficial to reduce the wear of the material on the first electrode 120.

[0096] It can be understood that the friction coefficient of the second wear-resistant conductive layer 123 can be 0.3, 0.32, 0.35, 0.38, 0.4, 0.42, 0.45, 0.48, 0.5, 0.52, 0.55, 0.58, 0.6 and any value within the range formed by any two of the above values.

[0097] In some embodiments, the conductivity of the second wear-resistant conductive layer 123 is 10μS / cm~500mS / cm. In this way, the second wear-resistant conductive layer 123 has a high conductivity, which can effectively form conduction between the contact part of the first electrode 120 and the power supply 140, which is conducive to introducing current into the material to heat the material. It can be understood that the conductivity of the second wear-resistant conductive layer 123 can be 10μS / cm, 50μS / cm, 100μS / cm, 200μS / cm, 500μS / cm, 800μS / cm, 1mS / cm, 100mS / cm, 200mS / cm, 300mS / cm, 400mS / cm, 500mS / cm and any value within the range formed by any two of the above values.

[0098] As shown in FIG1 , in some embodiments, the second electrode 130 extends radially along the material channel 111; there are multiple second electrodes 130, and the multiple second electrodes 130 are arranged at intervals along the circumference of the material channel 111. This is conducive to making the electric field distribution in the cross section of the material channel 111 more uniform, which is conducive to improving the uniformity of graphitization of the material.

[0099] Optionally, the second electrode 130 may be disposed in the middle and lower portion of the furnace body 110 , and the first electrode 120 and the second electrode 130 are disposed perpendicular to each other.

[0100] In some embodiments, the graphitization furnace 100 further includes a feeding unit, which includes a silo 151 and a material pipe 152. The silo 151 is disposed above the furnace body 110, and the silo 151 is connected to a material channel 111 in the furnace body 110 through the material pipe 152, and is used to feed the material to be graphitized into the material channel 111. Optionally, a material shut-off valve 153 may be further disposed at the connection between the silo 151 and the material pipe 152 to control the flow of the material in the material channel 111.

[0101] In some embodiments, the graphitization furnace 100 further includes a tail gas treatment unit 160, which is connected to the upper part of the material channel 111. The material entering the graphitization furnace 100 is a graphitizable carbonaceous material, such as petroleum coke, coal coke, and asphalt. After the material enters the material channel 111 of the graphitization furnace 100 from the feeding unit, it is graphitized in the material channel 111 to obtain a negative electrode graphite material product. The volatile tail gas emitted during the graphitization of the material is collected at the upper part of the material channel 111 and enters the tail gas treatment unit 160 for tail gas treatment.

[0102] In some embodiments, the graphitization furnace 100 further includes a cooling and discharging unit 170, which is disposed below the furnace body 110 and communicated with the bottom of the material channel 111, and is mainly used to cool the graphitized material and discharge the material at the same time. Specifically, as shown in FIG1 , the cooling and discharging unit 170 is provided with a water-cooling jacket, and the cooling medium may be circulating water. The graphitized material can be fully cooled and lowered in temperature by the cooling and discharging unit 170, and the cooled material can be discharged through a discharging system (not shown), and the discharging system may be a material discharge screw.

[0103] In one embodiment of the present application, a battery production device (not shown) is provided, which includes the graphitization furnace 100 described above in the present application, and the graphitization furnace 100 is used to produce negative electrode graphite materials for batteries. By adopting the graphitization furnace 100 described above in the present application, the battery production device of the present application has a longer service life.

[0104] It is understandable that the battery production equipment may include, in addition to the graphitization furnace 100 for producing the negative electrode graphite material of the battery, related equipment for producing other battery materials.

[0105] The battery production equipment may be a battery production line, and a plurality of equipment in the battery production line may be arranged in the same centralized location, or may also be arranged in separate different locations.

[0106] It should be noted that in the above embodiments of the present application, only some structures in the graphitization furnace 100 are listed. In addition to the structures involved in the above embodiments, the graphitization furnace 100 in the present application may also include other system structures of the graphitization furnace in the relevant technology, such as the electrical system of the electrode, the clamping system of the electrode, etc. The relevant technical solutions of each system can refer to the specific description in the relevant technology, and will not be discussed in detail herein.

[0107] In order to make the technical problems, technical solutions and beneficial effects solved by the present application clearer, the present application will be further described in detail in conjunction with the embodiments below. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present application and its applications. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0108] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0109] Embodiment 1:

[0110] (1) Preparation of the first electrode

[0111] The second binder phenolic resin, the second conductive agent graphene and carbon nanotube mixture (mass ratio 2:8) and the second wear-resistant filler poly L-glutamic acid and graphene mixture (mass ratio 3:7) were mixed at a mass ratio of 2.5:7.5:1, and the solvent ethanol was added and stirred evenly to form a second slurry with a solid content of 70%. The second slurry was coated on the graphite substrate and dried at 90°C to form a second wear-resistant conductive layer with a thickness of 20 μm. The thermal expansion coefficient of the second wear-resistant conductive layer is 20×10 -6 / ℃, the grinding number is 6000 revolutions, the friction coefficient is 0.3, and the conductivity is 400mS / cm.

[0112] The first binder epoxy resin, the first conductive agent graphene oxide and aluminum powder mixture (mass ratio 4:6) and the first wear-resistant filler poly L-glutamic acid and graphene mixture (mass ratio 3:7) were mixed in a mass ratio of 1:5:4, and the solvent ethanol was added and stirred evenly to form a first slurry with a solid content of 70%. The first slurry was coated on the second wear-resistant conductive layer and dried at 90°C to form a second wear-resistant conductive layer with a thickness of 30 μm, thereby obtaining a first electrode. The thermal expansion coefficient of the first wear-resistant conductive layer is 25×10 -6 / ℃, the grinding number is 9000 revolutions, the friction coefficient is 0.25, and the conductivity is 100mS / cm.

[0113] (2) Electrode assembly

[0114] The above-mentioned first electrode is used as the positive electrode of the graphitization furnace, installed in the material channel of the vertical graphitization furnace, and the first electrode is arranged along the extension direction of the material channel; a graphite electrode is used as the negative electrode, installed in the middle and lower part of the furnace body of the graphitization furnace, extending into the material channel and spaced apart from the first electrode, the negative electrode is arranged horizontally, the number of negative electrodes is 6, and multiple negative electrodes are spaced apart along the circumferential direction of the material channel to assemble into a graphitization furnace.

[0115] (3) Service life assessment

[0116] When the graphitization furnace is used to produce graphite, when the furnace resistance reaches 1.2 mΩ, the first electrode is inserted into the material channel until the furnace resistance is reduced to about 0.5 mΩ. According to the test, when the graphitization furnace is used to produce 300 tons of graphite, the first electrode is inserted into the material channel by a length of 16 cm.

[0117] It can be understood that, when producing the same amount of graphite, if the length of the first electrode extending into the material channel is shorter, the first electrode can be used for a longer time, indicating that the service life of the first electrode is longer; on the contrary, if the length of the first electrode extending into the material channel is longer, the first electrode can be used for a shorter time, indicating that the service life of the first electrode is shorter.

[0118] Embodiment 2:

[0119] (1) Preparation of the first electrode

[0120] The second binder bismaleimide resin, the second conductive agent graphene and carbon nanotube mixture (mass ratio 4:6) and the second wear-resistant filler poly L-glutamic acid and graphene mixture (mass ratio 4:6) were mixed in a mass ratio of 2:7:1, and the solvent ethanol was added and stirred evenly to form a second slurry with a solid content of 70%. The second slurry was coated on the graphite substrate and dried at 90°C to form a second wear-resistant conductive layer with a thickness of 20 μm. The thermal expansion coefficient of the second wear-resistant conductive layer is 30×10 -6 / ℃, the grinding number is 6500 revolutions, the friction coefficient is 0.35, and the conductivity is 350mS / cm.

[0121] The first binder vinyl resin, the first conductive agent graphene oxide and aluminum powder mixture (mass ratio 6:4) and the first wear-resistant filler poly L-glutamic acid and graphene mixture (mass ratio 4:6) are mixed in a mass ratio of 2:5:4, and the solvent ethanol is added and stirred to form a first slurry with a solid content of 70%. The first slurry is coated on the second wear-resistant conductive layer and dried at 90°C to form a second wear-resistant conductive layer with a thickness of 30 μm, thereby obtaining a first electrode. The thermal expansion coefficient of the first wear-resistant conductive layer is 30×10 -6 / ℃, the grinding number is 10000 revolutions, the friction coefficient is 0.3, and the conductivity is 90mS / cm.

[0122] (2) Electrode assembly

[0123] The above-mentioned first electrode is used as the positive electrode of the graphitization furnace, installed in the material channel of the vertical graphitization furnace, and the first electrode is arranged along the extension direction of the material channel; a graphite electrode is used as the negative electrode, installed in the middle and lower part of the furnace body of the graphitization furnace, extending into the material channel and spaced apart from the first electrode, the negative electrode is arranged horizontally, the number of negative electrodes is 6, and multiple negative electrodes are spaced apart along the circumferential direction of the material channel to assemble into a graphitization furnace.

[0124] (3) Service life assessment

[0125] When the graphitization furnace is used to produce graphite, when the furnace resistance reaches 1.2 mΩ, the first electrode is inserted into the material channel until the furnace resistance is reduced to about 0.5 mΩ. According to the test, when the graphitization furnace is used to produce 300 tons of graphite, the first electrode is inserted into the material channel by a length of 13 cm.

[0126] Embodiment 3:

[0127] (1) Preparation of the first electrode

[0128] The second binder cyanate resin, the second conductive agent graphene and graphene oxide mixture (mass ratio 5:5) and the second wear-resistant filler poly L-glutamic acid and graphene mixture (mass ratio 6:4) were mixed in a mass ratio of 3:6:1, and the solvent ethanol was added and stirred evenly to form a second slurry with a solid content of 70%. The second slurry was coated on the graphite substrate and dried at 90°C to form a second wear-resistant conductive layer with a thickness of 20 μm. The thermal expansion coefficient of the second wear-resistant conductive layer is 28×10 -6 / ℃, the grinding number is 7000 revolutions, the friction coefficient is 0.4, and the conductivity is 300mS / cm.

[0129] The first binder epoxy resin, the first conductive agent graphene oxide and aluminum powder mixture (mass ratio 4:6) and the first wear-resistant filler poly L-glutamic acid and graphene mixture (mass ratio 5:5) are mixed in a mass ratio of 3:5:4, and the solvent ethanol is added and stirred to form a first slurry with a solid content of 70%. The first slurry is coated on the second wear-resistant conductive layer and dried at 90°C to form a first wear-resistant conductive layer with a thickness of 30 μm, thereby obtaining a first electrode. The thermal expansion coefficient of the first wear-resistant conductive layer is 35×10 -6 / ℃, the grinding number is 11000 revolutions, the friction coefficient is 0.4, and the conductivity is 80mS / cm.

[0130] (2) Electrode assembly

[0131] The above-mentioned first electrode is used as the positive electrode of the graphitization furnace, installed in the material channel of the vertical graphitization furnace, and the first electrode is arranged along the extension direction of the material channel; a graphite electrode is used as the negative electrode, installed in the middle and lower part of the furnace body of the graphitization furnace, extending into the material channel and spaced apart from the first electrode, the negative electrode is arranged horizontally, the number of negative electrodes is 6, and multiple negative electrodes are spaced apart along the circumferential direction of the material channel to assemble into a graphitization furnace.

[0132] (3) Service life assessment

[0133] When the graphitization furnace is used to produce graphite, when the furnace resistance reaches 1.2 mΩ, the first electrode is inserted into the material channel until the furnace resistance is reduced to about 0.5 mΩ. According to the test, when the graphitization furnace is used to produce 300 tons of graphite, the first electrode is inserted into the material channel by a length of 10 cm.

[0134] Comparative Example 1:

[0135] (1) Electrode assembly

[0136] A graphite electrode is used as the positive electrode of the graphitization furnace and installed in the material channel of the vertical graphitization furnace, and the first electrode is arranged along the extension direction of the material channel; a graphite electrode is used as the negative electrode and installed in the middle and lower part of the furnace body of the graphitization furnace, extending into the material channel and spaced apart from the first electrode, the negative electrode is arranged horizontally, the number of negative electrodes is 6, and multiple negative electrodes are spaced apart along the circumferential direction of the material channel to assemble into a graphitization furnace.

[0137] (2) Service life assessment

[0138] When the graphitization furnace is used to produce graphite, when the furnace resistance reaches 1.2 mΩ, the first electrode is extended into the material channel until the furnace resistance is reduced to about 0.5 mΩ. According to the test, when the graphitization furnace is used to produce 300 tons of graphite, the first electrode is extended into the material channel by 210 cm.

[0139] Test method:

[0140] (1) Thermal expansion coefficient test

[0141] Provide a graphite sample with coating as a composite sample, and provide a graphite sample without coating as a matrix sample; use precision measuring tools to measure the cross-sectional area A of the coating on the composite sample respectively. c and the cross-sectional area of ​​the matrix A s ; Under the same experimental environment, the thermal expansion coefficient α of the matrix sample was measured simultaneously using a thermal expansion instrument s and the thermal expansion coefficient α of the composite sample b According to the formula α c =(αb A b -α s A s ) / A c Calculate the thermal expansion coefficient of the coating, where A b is the total cross-sectional area of ​​the composite sample.

[0142] (2) Grinding times test

[0143] The JM-1 paint film abrasion tester was used to evaluate the wear resistance of the coating under the action of friction at 23±2℃ and relative humidity of 50±5%. Specifically: a circular graphite sample with a coating was provided, the sample was mounted on the abrasion tester, and a trimmed rubber grinding wheel was used for sanding; during the test, the wear of the coating surface was observed, and the sanding was stopped when the coating was obviously worn or worn through, and the number of grinding revolutions at this time was recorded.

[0144] (3) Friction coefficient test

[0145] Take two 200mm×80mm coated graphite samples, fix one of them on the test plate of PCF-03 friction coefficient tester with double-sided tape, and fix the other sample on a special slider after cutting it to the appropriate size according to the test requirements; gently place the slider with the sample fixed on the center of the sample on the test plate, insert the vertical pin at the front of the slider into the sensor pin shaft hole, and ensure that the equipment sensor returns to the origin; press the test button to start the test, and the instrument automatically records the data and calculates the friction coefficient.

[0146] (4) Conductivity test

[0147] Provide a graphite sample with a coating, ensure that the coating surface is flat, clean, and free of oil, impurities, etc., to ensure good contact between the probe and the coating; gently place the four probes of the four-probe tester on the coating surface, so that the probes are in close contact with the coating and the spacing between the probes is kept equal; turn on the tester, set a suitable current value, pass current through the two outer probes through a constant current source, and measure the potential difference between the two middle probes at the same time; according to the measured current I, voltage U and probe spacing S, substitute into the formula ρ=2πSU / I to calculate the resistivity ρ; and then obtain the coating conductivity σ=1 / ρ.

[0148] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A graphitization furnace, characterized in that: include: A furnace body, wherein a material channel is arranged in the furnace body; A first electrode is arranged along the extension direction of the material channel and is partially located in the material channel; the first electrode comprises a substrate and a first wear-resistant conductive layer arranged on the surface of the substrate; The second electrode has a polarity opposite to that of the first electrode; the second electrode extends into the material channel and is spaced apart from the first electrode.

2. The graphitization furnace according to claim 1, characterized in that: The first wear-resistant conductive layer includes a first adhesive, a first conductive agent and a first wear-resistant filler.

3. The graphitization furnace according to claim 2, characterized in that: Meet one or more of the following: (1) The first binder includes one or more of phenolic resin, epoxy resin, bismaleimide resin, vinyl resin and cyanate resin; (2) The first conductive agent includes one or more of a carbon material, a metal material and a conductive polymer; (3) The first wear-resistant filler includes one or more of poly-L-glutamic acid graphene composite, boron carbide powder, silicon carbide powder, metal powder and aluminum oxide powder.

4. The graphitization furnace according to claim 3, characterized in that: The carbon material includes one or more of graphene, graphene oxide, carbon fiber and carbon nanotube; the metal material includes one or more of silver powder, copper powder, silver fiber and copper fiber.

5. The graphitization furnace according to any one of claims 2 to 4, characterized in that: The mass ratio of the first binder, the first conductive agent and the first wear-resistant filler is 1-3:5-7:2-4.

6. The graphitization furnace according to any one of claims 1 to 4, characterized in that: The thickness of the first wear-resistant conductive layer is 30 μm to 200 μm.

7. The graphitization furnace according to any one of claims 1 to 4, characterized in that: The thermal expansion coefficient of the first wear-resistant conductive layer is 10×10 -6 / ℃~100×10 -6 / ℃.

8. The graphitization furnace according to any one of claims 1 to 4, characterized in that: The first wear-resistant conductive layer can be rotated 9000 to 11000 times under the conditions of 23±2°C and 50±5% relative humidity.

9. The graphitization furnace according to any one of claims 1 to 4, characterized in that: The friction coefficient of the first wear-resistant conductive layer is 0.2-0.

4.

10. The graphitization furnace according to any one of claims 1 to 4, characterized in that: The conductivity of the first wear-resistant conductive layer is 50 μS / cm-1000 mS / cm.

11. The graphitization furnace according to any one of claims 1 to 4, characterized in that: The first electrode further includes a second wear-resistant conductive layer, and the second wear-resistant conductive layer is arranged between the substrate and the first wear-resistant conductive layer.

12. The graphitization furnace according to claim 11, characterized in that: The material of the second wear-resistant conductive layer includes a second binder, a second conductive agent and a second wear-resistant filler.

13. The graphitization furnace according to claim 12, characterized in that: Meet one or more of the following: (1) The second binder includes one or more of phenolic resin, epoxy resin, bismaleimide resin, vinyl resin and cyanate resin; (2) The second conductive agent includes one or more of a carbon material, a metal material and a conductive polymer; (3) The second wear-resistant filler includes one or more of poly-L-glutamic acid graphene composite, boron carbide powder, silicon carbide powder, metal powder and aluminum oxide powder.

14. The graphitization furnace according to claim 12 or 13, characterized in that: The mass ratio of the second binder, the second conductive agent and the second wear-resistant filler is 2-4:4-8:1-2.

15. The graphitization furnace according to claim 11, characterized in that: The thickness ratio of the second wear-resistant conductive layer to the first wear-resistant conductive layer is 1:1-8.

7.

16. The graphitization furnace according to claim 15, characterized in that: The thickness ratio of the second wear-resistant conductive layer to the first wear-resistant conductive layer is 1:1-4.

3.

17. The graphitization furnace according to claim 11, characterized in that: The thickness of the second wear-resistant conductive layer is 20 μm to 40 μm.

18. The graphitization furnace according to claim 11, characterized in that: The ratio of thermal expansion coefficients of the second wear-resistant conductive layer to the first wear-resistant conductive layer is 1:1-1.

5.

19. The graphitization furnace according to claim 18, characterized in that: The ratio of thermal expansion coefficients of the second wear-resistant conductive layer to the first wear-resistant conductive layer is 1:1-1.

2.

20. The graphitization furnace according to claim 11, characterized in that: The thermal expansion coefficient of the second wear-resistant conductive layer is 5×10 -6 / ℃~30×10 -6 / ℃.

21. The graphitization furnace according to claim 11, characterized in that: The second wear-resistant conductive layer can be rotated 6000 to 8000 times under the conditions of 23±2° C. and 50±5% relative humidity.

22. The graphitization furnace according to claim 11, characterized in that: The friction coefficient of the second wear-resistant conductive layer is 0.3-0.

6.

23. The graphitization furnace according to claim 11, characterized in that: The electrical conductivity of the second wear-resistant conductive layer is 10 μS / cm-500 μS / cm.

24. The graphitization furnace according to any one of claims 1 to 4, 12 to 13, and 15 to 23, characterized in that: The second electrode extends in a radial direction of the material channel.

25. The graphitization furnace according to any one of claims 1 to 4, 12 to 13, and 15 to 23, characterized in that: There are multiple second electrodes, and the multiple second electrodes are arranged at intervals along the circumference of the material channel.

26. The graphitization furnace according to any one of claims 1 to 4, 12 to 13, and 15 to 23, characterized in that: The first electrode is a positive electrode, and the second electrode is a negative electrode.

27. A battery production device, characterized in that: A graphitization furnace comprising any one of claims 1 to 26, wherein the graphitization furnace is used to produce graphite materials for batteries.

Citation Information

Patent Citations

  • Composite ceramic graphite electrode

    CN104177128A

  • Anti-corrosion conductive ceramic electrode material for sewage and sludge treatment and preparation method thereof

    CN105523761A

  • Protective film, underground space electrolyte reservoir, preparation method of underground space electrolyte reservoir, leak detection system and leak detection method of leak detection system

    CN116111137A

  • Graphitization furnace and battery production system

    CN118670134A

  • Graphitization furnace and battery preparation device

    WO2024178627A1